Spatial and Temporal Analysis of Seasonal Rainfall on the East Coast of North Sumatra, Indonesia - Nuzul Hijri Darlan; Sigit Supadmo Arif; Putu Sudira; Bayu Dwi Apri Nugroho (Faculty of Geography, Universitas Gadjah Mada, 2020)
The east coast of North Sumatra has lower rainfall than the central (Bukit Barisan) and the west coast. Meanwhile, the literature on the influence of climate phenomena, such as El Nino, La Nina, and positive/negative IOD, on the rainfall distribution in North Sumatra remains quite limited. This paper aims to describe the spatial distribution of seasonal rainfall on the east coast of North Sumatra and its correlation with ENSO and the IOD. Hopefully, the spatial analysis of seasonal rainfall and its correlation to ENSO and IOD can improve the understanding on rainfall distribution and the influenced factors in the study area. For 16 years (1999–2014), the monthly rainfall data at 52 rain gauge stations that passed the homogeneity test were divided into the seasonal 6-month and 4-month. Hereafter, the seasonal rainfall was spatially analyzed with the Inverse Distance Weighting (IDW) method using ArcMap software. The spatial analysis results can clearly describe the rainfall dynamics and its anomalies, therefore, can be more easily understood. The repetition of rainfall anomaly patterns can be seen in January to June (JFMAMJ), January to April (JFMA), and May to August (MJJA), which occurs in 3–4 years. Furthermore, the Pearson-correlation analysis shows that SOI has a strong positive correlation on JFMAMJ (0.529), JFMA (0.485), and MJJA (0.366), while IOD has a strong positive correlation on MJJA (0.512) and negative on September to December - SOND (-0.341).